1983
DOI: 10.2355/isijinternational1966.23.43
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Time of Refining Vessels Stirred by Gas Injection

Abstract: SynopsisCorrelation between mixing time (v) and mixing power density (e) for gas agitation is theoretically developed from the view point of transport phenomena and the theoretical results were confirmed by the water model experiments. Fluid motion in the vessel agitated by gas injection can be classified into two major flows. One is a flow predominated by viscous force, in which v is in proportion to 05 and v does not depend on the vessel size. The other is a flow predominated by inertia force or turbulent vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
3

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 1 publication
2
65
0
3
Order By: Relevance
“…(24) are only specific to vessel dimension and types of gas liquid systems, but not to the geometry or dimension of the gas injection devices. [32][33][34][35][36][37] Numerous theoretical and experimental studies on mixing phenomena have been reported in the literature and a great deal of these have already been summarized in the earlier review. 1) Many of these investigations were primarily concerned with developing models of mixing time in terms of the key operating variables namely, gas flow rate, Q, vessel radius, R, and depth of liquid in the ladle, L. Apart from a few studies on asymmetrically located plugs/nozzle, a vast majority of these were carried out on axi-symmetrical or central gas injection configurations.…”
Section: Structure Of Gas-liquid Plume and Plumementioning
confidence: 99%
“…(24) are only specific to vessel dimension and types of gas liquid systems, but not to the geometry or dimension of the gas injection devices. [32][33][34][35][36][37] Numerous theoretical and experimental studies on mixing phenomena have been reported in the literature and a great deal of these have already been summarized in the earlier review. 1) Many of these investigations were primarily concerned with developing models of mixing time in terms of the key operating variables namely, gas flow rate, Q, vessel radius, R, and depth of liquid in the ladle, L. Apart from a few studies on asymmetrically located plugs/nozzle, a vast majority of these were carried out on axi-symmetrical or central gas injection configurations.…”
Section: Structure Of Gas-liquid Plume and Plumementioning
confidence: 99%
“…The gas flow rates applied in the present investigation were so chosen that the corresponding specific energy input rate to the systems were of the order of 10 Ϫ3 W/kg 10) (typical of ladle metallurgy steelmaking operations). For such energy input rate values, typically big gas envelopes were seen to form in the vicinity of the orifice.…”
Section: Present Workmentioning
confidence: 99%
“…Similarly, physical modeling of industrial ladle processing operations were also carried out under steady flow conditions, ensured by blowing the gas through the bath for a prolonged period of time prior to any detailed measurements. [1][2][3][4][5][6][7][8][9][10][11][12] Thus, practically very little or no information on ladle hydrodynamics, under transient flow conditions (which is relevant particularly during the initial as well as the post gas injection period) has been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] To analyze phenomena associated with the agitation of liquid baths, the determination of the mixing time is very important. [11][12][13][14][15][16][17][18][19][20][21] A number of studies [18][19][20][21][22] have reported that the value of the mixing time obtained experimentally is dependent on the location of the measuring probe and the tracer injection. Murthy has shown that the degree of mixing in the bath changes as the operating conditions is varied.…”
Section: Introductionmentioning
confidence: 99%